PROTOTYPE BAHAN AJAR BAHASA INDONESIA BERORIENTASI DUNIA KERJA KEPARIWISATAAN UNTUK SISWA KELAS X SMK - nurjaya, gede (Journal of Education Reseach and Evaluation, 2017)
This  research and development was done with the aim of developing tourism sector oriented instructional material for the tenth grade students at SMK Program Keahlian  UPW in Denpasar City. To achieve  the aim, a study was done to identify  the tourism instructional material and Indonesian  material that is relevant to the development of  Indonesian instructional material for the tenth grade students at SMK  Program Keahlian Usaya Pelayanan Wisata in Denpasar City.  In the second year, using document analysis method and panel group discussion, Indonesian instructional material for the tenth grade students at SMK  Program Keahlian Usaya Pelayanan Wisata in Denpasar City had been developed The basic framework of the material  is as follows: (1) the use of thematic  approach to cover the theme of  tourism in the Indonesian textbook, (2) the use of  text based Indonesian instructional material  development, (3) the use of scientific approach in implementing text based instructional material. The prototype  designed  has  good validity when it was judged by relevant judges. With the findings, it is suggested  that in developing  instructional material with other orientations  the instructional material development  has to be adapted to  the design of the prototype found in this study.